Acquired Long QT Syndrome and Torsades de Pointes after Mitral Valve Replacement Surgery - Rodríguez-Artuza , Carlos; Barajas, Héctor; Rivera, José; Clavel, Emilio; Labarca, Mayela (JOURNAL OF CARDIAC ARRHYTHMIAS, 2021)
Acquired long QT syndrome (aLQTS) can occur in up to one third of patients undergoing cardiac surgery and is often undisclosed. We present a case of a 55-year-old male patient admitted to our center for mitral valve replacement surgery, and, during the postoperative period, a long QT greater than 600 ms was confirmed and in the Holter monitoring Torsade de Pointes (TdP) was evidenced. The patient received appropriate medical treatment and was discharge in stable clinical conditions.